2018
DOI: 10.1007/s00018-018-2895-8
|View full text |Cite
|
Sign up to set email alerts
|

ENL: structure, function, and roles in hematopoiesis and acute myeloid leukemia

Abstract: ENL/MLLT1 is a distinctive member of the KMT2 family based on its structural homology. ENL is a histone acetylation reader and a critical component of the super elongation complex. ENL plays pivotal roles in the regulation of chromatin remodelling and gene expression of many important proto-oncogenes, such as Myc, Hox genes, via histone acetylation. Novel insights of the key role of the YEATS domain of ENL in the transcriptional control of leukemogenic gene expression has emerged from whole genome Crisp-cas9 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…For all these transcription factors, only one significant binding event (MLLT1) was detected surrounding methylated ZBTB33 binding sites in both cell lines (Figure 3 left). Interestingly, MLLT1, also known as ENL, is a critical component of the super elongation complex and also a histone acetylation reader [27]. The co-occupancy of MLLT1 with ZBTB33 in methylated binding sites suggests the potential of transcriptional regulation in these regions.…”
Section: Co-occupancy Of Transcription Factors Surrounding Zbtb33 Binmentioning
confidence: 99%
“…For all these transcription factors, only one significant binding event (MLLT1) was detected surrounding methylated ZBTB33 binding sites in both cell lines (Figure 3 left). Interestingly, MLLT1, also known as ENL, is a critical component of the super elongation complex and also a histone acetylation reader [27]. The co-occupancy of MLLT1 with ZBTB33 in methylated binding sites suggests the potential of transcriptional regulation in these regions.…”
Section: Co-occupancy Of Transcription Factors Surrounding Zbtb33 Binmentioning
confidence: 99%
“…An epigenetic upregulation of FKBP5 could promote NF-kB activation [ 30 ]. STAT3-NFkB activity is involved in chemoresistance in MM cells [ 31 ], and NFkB was shown to be constitutively active as a result of asbestos-induced chronic inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MLLT1 gene encodes the ENL protein, a histone acetylation reader component of the super elongation complex (SEC), which promotes transcription at the elongation stage by suppressing transient pausing by the polymerase at multiple sites along the DNA. In acute myeloid leukemia, MLLT1 regulates chromatin remodeling and gene expression of many important proto-oncogenes [ 31 ]. Yoshikawa and colleagues suggested that mesothelioma may be the consequence of the somatic inactivation of chromatin-remodeling complexes and/or histone modifiers, including MLLT1 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[44] Another intermediary, MLLT1 is a component of the super elongation complex (SEC), a complex required to increase the catalytic rate of RNA polymerase II transcription by suppressing transient pausing by the polymerase at multiple sites along the DNA. [45] Kruppel-like factor 9 (KLF9), a TF, is critical for the inhibition of growth and development of tumors. KLF9 role is notable in lung and pancreas tumors.…”
Section: Discussionmentioning
confidence: 99%